2008
DOI: 10.1002/jnr.21915
|View full text |Cite
|
Sign up to set email alerts
|

Content of endoplasmic reticulum and Golgi complex membranes positively correlates with the proliferative status of brain cells

Abstract: Although the molecular and cellular basis of particular events that lead to the biogenesis of membranes in eukaryotic cells has been described in detail, understanding of the intrinsic complexity of the pleiotropic response by which a cell adjusts the overall activity of its endomembrane system to accomplish these requirements is limited. Here we carried out an immunocytochemical and biochemical examination of the content and quality of the endoplasmic reticulum (ER) and Golgi apparatus membranes in two in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In this regard, the levels found in our study imply a greater participation of phosphorus during the development of neural tissue (9). Silvestre et al also showed that total lipid phosphorus content is higher in the embryonic brain than in adult brain cells (16). As the developing brain contains superior concentrations of phosphate groups belonging to lecithins, cephalins and sphingomyelins, this could explain the different values found in our study.…”
Section: Implications Of Trace Elements Detected In Cerebral Organoidmentioning
confidence: 43%
“…In this regard, the levels found in our study imply a greater participation of phosphorus during the development of neural tissue (9). Silvestre et al also showed that total lipid phosphorus content is higher in the embryonic brain than in adult brain cells (16). As the developing brain contains superior concentrations of phosphate groups belonging to lecithins, cephalins and sphingomyelins, this could explain the different values found in our study.…”
Section: Implications Of Trace Elements Detected In Cerebral Organoidmentioning
confidence: 43%
“…In this regard, the levels found in our study imply a greater participation of P during the development of neural tissue (Rajan et al, 1997). Silvestre and colleagues (2009) also showed that total lipid P content is higher in the embryonic brain than in adult brain cells (Silvestre, Maccioni & Caputto, 2009). The developing brain contains superior concentrations of phosphate groups belonging to lecithins, cephalins, and sphingomyelins, this could explain the different values found in our study.…”
Section: Sr-xrf Is a Suitable Technique To Scan And Image Trace Elemesupporting
confidence: 44%
“…No difference in the labeling of phospholipids was observed between both genotypes, even after the addition of recombinant c-Fos to the assay medium indicating that the membrane biosynthesis machinery produces membrane at a rate high enough to be independent of its activation by c-Fos. In line with this possibility is the observation that the content of endoplasmic reticulum and Golgi membranes, where the bulk of membrane lipid synthesis occurs, is significantly higher in developing brain that in adult brain (Figure 11C ) [ 36 ].…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that at early embryonic stages of brain development in which high rates of proliferation occur, the content of Golgi and ER membranes is significantly higher than that in adult brain cells [ 36 ]. So, we examined the expression of GM130 as a marker of the Golgi apparatus and of GRP78 BiP as a marker of the ER in E14.5 c-fos +/+ and c-fos −/− embryos and adult mice brain.…”
Section: Resultsmentioning
confidence: 99%